Cryptographic salting for security enhancement of double random phase encryption schemes - Vélez Zea, Alejandro (2017)
Security in optical encryption techniques is a subject of great importance, especially in light of recent reports of successful attacks. We propose a new procedure to reinforce the ciphertexts generated in double random phase encrypting experimental setups. This ciphertext is protected by multiplexing with a 'salt' ciphertext coded with the same setup. We present an experimental implementation of the 'salting' technique. Thereafter, we analyze the resistance of the 'salted' ciphertext under some of the commonly known attacks reported in the literature, demonstrating the validity of our proposal.